The Role of Capital Structure in Determining the Value of FNB Companies: Peran Struktur Modal Mediasi Penentu Nilai Perusahaan FNB - Puspitasari, Devina Eka; Fitriyah, Hadiah (Indonesian Journal of Innovation Studies, 2025)
General Background The intense competition in the industrial sector necessitates a focus on maximizing firm value to attract investors. Specific Background Profitability, liquidity, and company growth are key determinants of company value, with capital structure playing a crucial financial role. Knowledge Gap Prior studies show conflicting results regarding the direct influence of these financial ratios on firm value, creating a need for a clearer causal model. Aims This study examines the mediating role of capital structure in the relationship between profitability, liquidity, company growth, and firm value in the Indonesian Food and Beverages sector (2019-2022). Results Findings show that while profitability directly affects firm value, liquidity and company growth do not. Crucially, capital structure successfully mediates the relationship between all three independent variables and firm value. Novelty This research contributes by incorporating company growth and capital structure as a mediator to reconcile the existing empirical inconsistencies. Implications The results highlight that optimal capital structure management is vital for the F&B sector, proving to be the essential link for profitability, liquidity, and growth to ultimately increase company value. Highlights Profitability is the only variable with a direct positive effect on firm value. Capital structure successfully mediates the link between all independent variables and firm value. Liquidity and Company Growth require capital structure to positively influence firm value. Keywords: Capital Structure, Profitability, Liquidity, Company Growth, Company Value